La eficiencia productiva como indicador de desempefio empresarial - Suárez R., Otto (2014)
This article presents the concept of productive efficiency as a tool to determine the productive performance of a firm, focusing on the definition and measurement of technical efficiency as a proxy for productive efficiency. Starting with concept reviews, emphasis is placed on the importance of analyzing technical efficiency so the units of production can have an extra tool, in addition to the conventional economic and financial indicators, that allows them to assess their technical and productive performance. The main methods used for the measurement of technical efficiency are also succinctly reviewed, as well as the potential applications of the tool in different fields of production. The authors expect to foster interest and research in the topic of efficiency that would lead to projects applied to current productive issues at firms' level.